RESEARTCH OF A MODEL FOR APPLICATION OF ENGINEERING LOGISTICS IN THE MAINTENANCE SECTOR: RESEARTCH OF A MODEL FOR APPLICATION OF ENGINEERING LOGISTICS IN THE MAINTENANCE SECTOR - Peeva , Svetla (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The present study aims to present not logistics as a service in itself, but the logistics approach in a company falling into the services sector, the end product of which is the performance of technical activities. The object of study is the sector of technical services in particular the construction and future maintenance of building installations for automatic control.